The association between childbirth-related fear, childbirth readiness, and fertility intentions, and childbirth readiness as the mediator - Tieying Zeng; Bingbing Li; Ke Zhang; Ye Chen; Mengmei Yuan; Meiliyang Wu; Huimin Zhao; Zining Zhu; Dandan Ju (BMC, 2023)
Abstract Background Fertility intentions have been proved to be a reliable predictor of actual fertility behaviour. Also, childbirth-related fear (CBRF) has been proven to be negatively associated with childbirth readiness and fertility intentions among women, while childbirth readiness was positively related to fertility intentions. However, the associations and potential mechanisms between CBRF, childbirth readiness, and fertility intentions remain unknown. This study aimed to investigate the unique association between CBRF, childbirth readiness, and fertility intentions and whether childbirth readiness would mediate the relationship between CBRF and fertility intentions. Method A cross-sectional study of women (N = 1119, aged 16-53 years) who gave birth within 72 h was conducted. Using a convenience sampling, women were recruited from obstetric wards-10 comprehensive hospitals and 3 specialized hospitals in 7 provinces in mainland China. Pearson correlation was used to examine the relationship between CBRF, childbirth readiness, fertility intentions, and social support. Multivariate linear regression was further used to analyze the association between demographic and personal characteristics, CBRF, childbirth readiness, and fertility intentions. Mediation analysis was used to examine whether childbirth readiness mediates the relationship between CBRF and fertility intentions. Results Women with high childbirth readiness (β = 0.09, P = 0.002) had higher fertility intentions. However, women with high CBRF (β = − 0.17, P < 0.001) were more likely to have lower fertility intentions. CBRF had both direct and indirect effects on the level of fertility intentions. As predicted, childbirth readiness mediated the relationship between CBRF and the level of fertility intentions (estimate = − 0.012, 95% bootstrap CI: − 0.021 to − 0.005). Higher CBRF was associated with lower scores of childbirth readiness, which was associated with lower levels of fertility intentions. Conclusions This study established the evidence that CBRF had both direct and indirect effects on the level of fertility intentions and childbirth readiness mediated the relationship between CBRF and the level of fertility intentions. Specifically, higher CBRF was associated with lower scores of childbirth readiness, which was associated with lower levels of fertility intentions. This finding suggested that it is important for health policymakers and health providers to pay more attention to improving women's childbirth readiness, which might reduce the negative influence of CBRF on fertility intentions, thus strengthening their fertility intentions.